Level of Tourist Confidence with the Loyalty of Tourism Object Managers: A Case Study of the Kayumanis Village Trokon River Tourism Object - Dina, Dwita Prisdinawati; Mira Yanuarti; Sundari Aditiya (English and Tourism Studies, 2023)
The authors want to know how satisfied tourists are with the loyalty of the Trokon River tourism object's management in Kayumanis Village in light of this background. The motivation behind the exploration is to distinguish traveler appraisals concerning the degree of guest assumptions and the presentation of guest fascination for the Trokon Waterway visit in Kayu Cinnamon Town. This research analysis employs qualitative and quantitative analysis as its method. Subjective examination, in particular, breaks down issues connected with research as portrayals and elaborations. Quantitative examination, precisely ascertaining with assurance the information acquired from dispersing polls and the apparatus utilized, is the Fishbein technique; Fishbein's definition is the most well-known property model. Based on a set of beliefs regarding the attributes of manager loyalty weighted by an evaluation of these attributes, the Fishbein method is used to determine the level of tourist/visitor satisfaction with the loyalty of tourism object managers. The consequences of this examination demonstrate that the reliability of the Trokon, The travel industry Item supervisors, is all around seen by sightseers. This cannot be separated from the characteristics of a Manager's loyalty. The fact that the tourism object manager's loyalty value is not significant despite being to the right (positive) of the secant line is noteworthy. This can be a record for pioneers and executives to additionally work on the nature of administration from existing assets because of these traits.